Why smallholders plant native timber trees away from the forest margin: Lessons from Leyte, the Philippines - Santos Martín, Fernando; Bertomeu M; Noordwijk, Meine van; Navarro, Rafael (ASB Partnership for the Tropical Forest Margins, 2011)
As long as natural forests can be accessed as local sources of timber, there is little incentive for farmers to grow timber on their own land. Early successes with national programs for farmer tree planting in the Philippines were achieved with fast growing trees that brought disappointingly low levels of income once harvested, as the quality of wood was low. Meanwhile, some farmers took the initiative to grow high-value, slower-growing native timbers on their farms, planting trees between their maize. What are the prospects for this? Which types of farmers are doing it? Is it profitable? What policy measures could support or enhance such agroforestation of the landscape? A recent study looked at several of these questions at the island of Leyte in the Philippines. The results have implications for other forest margin locations.